Antithrombotic treatment is associated with intraplaque haemorrhage in the atherosclerotic carotid artery: a cross-sectional analysis of The Rotterdam Study. (27th July 2018) - Mujaj, Blerim; Bos, Daniel; Muka, Taulant; Lugt, Aad van der; Ikram, M Arfan; Vernooij, Meike W; Stricker, Bruno H; Franco, Oscar H
Abstract: Aims: Antithrombotic treatment plays a key role in stroke prevention, but their direct effects on the composition of carotid artery atherosclerotic plaques are unknown. To investigate the association of antithrombotic treatment with carotid artery plaque composition, with a specific focus on an intraplaque haemorrhage (IPH). Methods and results: From the population-based Rotterdam Study, 1740 participants with carotid atherosclerosis on ultrasound (mean age 72.9 years, 46.0 women) underwent magnetic resonance imaging of the carotid arteries to assess plaque composition. Information on the use of oral anticoagulants [vitamin K antagonists (VKA)] and antiplatelet agents (salicylates), including duration of use and dosage, was obtained from pharmacy records for all participants. We used logistic regression models to assess the association between the use of anticoagulants and antiplatelet agents, and the different plaque components adjusting for confounders. Current and past use of VKA [adjusted odds ratio (OR): 1.88, 95% confidence interval (CI): 0.74–4.75 and OR 1.89, 95% CI: 0.91–3.93] and antiplatelet agents (OR: 1.22, 95% CI: 0.91–1.62), and (OR: 1.23, 95% CI: 0.86–1.75) showed positive trend with a higher presence of IPH. Also, a longer duration of use was associated with a higher frequency of IPH (OR: 3.15, 95% CI: 1.23–8.05) for the use of VKA, and longer duration of the use for antiplatelet agents showed a positive trend (OR: 1.21, 95% CI: 0.88–1.67). We also found that higher levels of international normalized ratio above 2.97 for VKA (OR: 1.48, 95% CI: 1.03–2.15) and higher daily defined dosage than 1.0 for antiplatelet agents (OR: 1.50, 95% CI: 1.21–1.87) were related to a higher frequency of IPH. We found no association with lipid core or calcification. Conclusions: The use of antithrombotic treatment relates to a higher frequency of IPH in carotid atherosclerotic plaques.